SENP1 and SENP2 affect spatial and temporal control of sumoylation in mitosis - Caelin Cubeñas-Potts; Jacqueline Goeres; Michael J. Matunis (2013)
Sumoylation of centromere, kinetochore, and other mitotic chromosome-associated proteins is essential for chromosome segregation. The mechanisms regulating spatial and temporal sumoylation of proteins in mitosis, however, are not well understood. Here we show that the small ubiquitin-related modifier (SUMO)-specific isopeptidases SENP1 and SENP2 are targeted to kinetochores in mitosis. SENP2 targeting occurs through a mechanism dependent on the Nup107-160 subcomplex of the nuclear pore complex and is modulated through interactions with karyopherin α. Overexpression of SENP2, but not other SUMO-specific isopeptidases, causes a defect in chromosome congression that depends on its precise kinetochore targeting. By altering SENP1 kinetochore associations, however, this effect on chromosome congression could be phenocopied. In contrast, RNA interference-mediated knockdown of SENP1 delays sister chromatid separation at metaphase, whereas SENP2 knockdown produces no detectable phenotypes. Our findings indicate that chromosome segregation depends on precise spatial and temporal control of sumoylation in mitosis and that SENP1 and SENP2 are important mediators of this control.